Assessment of matrix effects associated with Fe isotope analysis using 266 nm femtosecond and 193 nm nanosecond laser ablation multi-collector inductively coupled plasma mass spectrometry. Issue 1 (15th November 2017) - Zheng, Xin-Yuan; Beard, Brian L.; Johnson, Clark M.
Abstract : The nature of matrix effects during in situ Fe isotope analysis using fs- and ns-laser ablation (LA) was characterized and compared. Abstract : This study evaluated matrix effects during Fe isotope analysis using a 266 nm femtosecond (fs) laser and a 193 nm nanosecond (ns) laser coupled to a multi-collector ICP-MS. During 150 second spot analysis on pyrite, Fe isotope fractionation was not observed for fs-laser ablation (fs-LA), but was evident for ns-LA. The observed downhole Fe isotope fractionation during ns-LA is caused by multiple processes comprising ablation, transport, and ionization in the ICP. Contrary to the common perception of "matrix-free" analysis, matrix effects clearly exist during fs-LA analysis; small deviations of up to ∼0.2‰ in the measured 56 Fe/ 54 Fe ratios from the true value of magnetite grains with ≥∼8 wt% impurities were resolved using a nearly pure magnetite as the bracketing standard. Moreover, inaccurate and imprecise 56 Fe/ 54 Fe results were obtained when magnetite and pyrrhotite was measured against a non-matrix-matched standard (pyrite or Fe metal). The observed matrix effects during fs-LA cannot be explained by formation of a large heat-affected zone during ablation, but result from the influence of different chemical compositions of samples and standards on space-charge effects in the ICP-MS. Such matrix effects can be largely suppressed by water addition during analysis at a price of reduced sensitivity, so that precise and accurate Fe isotope analysis to a ∼0.1‰ level can be routinely achieved under "wet" conditions without matrix-matching between sample and standard. These results may reconcile dramatically different precisions previously reported for Fe isotope analysis by fs-lasers, and also highlight fs-LA-MC-ICP-MS as an appealing option for in situ Fe isotope analysis on samples with complex matrices and high-symmetry minerals, both of which encounter significant analytical difficulties using secondary ion mass spectrometry (SIMS). For ns-LA, in addition to similar composition-related matrix effects experienced by fs-LA in the ICP, matrix effects also originate from ablation-related processes that produce sample particles with matrix-dependent size distributions and, often, larger aerodynamic sizes, resulting in highly inaccurate 56 Fe/ 54 Fe results during non-matrix-matched analysis under "dry" conditions. The collective matrix effects during Fe isotope analysis by ns-LA cannot be fully suppressed by water addition, therefore, matrix matching is required for accurate Fe isotope analysis by ns-LA.